Pass Word Based Circuit Breaker. - Asiimwe, Johnson (Kabale University, 2023)
This project focuses on the safety of the lineman while working, so they do not feel the sudden electric shocks. As the lineman has to deal with live wires very often, the probability of critical accidents is already very high. Therefore, it was necessary to provide a safely system of protection to avoid the accidents that may occurs in case of miss coordination between the lineman and station or control staff. This project designed to give a high security system and that in switching off the meanly line with entering a password with a help of keypad. And here we have a safety system to work on it. When the lineman staff get finished what they work on, they can activate the line by either of two ways, entering the same password that added before using keypad on station, or by sending SMS message including the password that selected before, and here we have a very important feature that is gain time.